Clinically Effective Regenerative Therapy for Primary Endodontic Lesions with Secondary Periodontal Lesions: A Case Report - Amalia, Martina; Budi, Budi; Kurmaena, Iceu Estu; Yanti, Nevi; Nurcahyanti, Hesty; Nasution, Aini Hariyani (UI Scholars Hub, 2023)
The diagnosis and prognosis of teeth with endo-perio lesions present a major challenge for dentists. Proper diagnosis is critical in determining treatment and the long-term prognosis. However, treating complex endodontic and periodontal lesions is one of the most common challenges in current clinical practice. The coexistence of pulpal and periodontal tissue damage may complicate diagnosis and further influence dental prognosis. This article consists of a case report evaluating the efficacy of xenografts and resorbable membrane pericardium in treating bifurcation lesions associated with periodontal lesions of the left mandibular first molar. A 22-year-old female patient was referred by conservative dentistry with complaints of gingival swelling on tooth 36 with furcation involvement associated with periodontal lesions. A gingivectomy was performed after the first stage of periodontal therapy because gingival swelling precluded endodontic treatment. After 3 months of endodontic treatment, the grade II bifurcated lesion had not yet healed, so regenerative surgery using xenografts and a resorbable pericardial membrane was performed. Periodontal treatment showed no gingival inflammation, and radiographic evidence showed bone improvement. Endo-perio lesions are complex in etiology and require a high degree of expertise to identify and treat them. Therefore, effective treatment of lesions requires collaboration between various multidisciplinary disciplines.